PERSEPSI ANAK SEKOLAH DASAR MENGENAI BAHAYA ROKOK (STUDI PADA ANAK SEKOLAH DASAR DI PERKOTAAN DAN PEDESAAN DI KOTA DEMAK) - Risti Dwi Arfiningtyas; Trixie Salawati (Universitas Muhammadiyah Semarang, 2015)
Background : Smokers early ages 10-14 years of age is increasing from year to year. Basedon the characteristics of smokers living in rural areas have a higher percentage of urban areas, the prevalence of early age smokers in rural areas has increased each year. This study aims to determine the perceptions of elementary school children about the dangers of smoking in the urban and rural. Method : This type of research is comparative with the independent variable is the urban and ruralareas and the dependent variable is the perception of the dangers of smoking. The samples in this study were primary school children in grade 4 and 5 at SDN Bintoro 1 and SDN Donorojo 2 Demak taken with proportional random sampling technique with a number of respondents was 56 respondents. Analysis of the data using two different test mean (T Independent).Results : Results of Independent T test shows there is a difference between the perceptions of primary school children in urban and rural areas about the dangers of smoking. Primary school children in urban areas have more positive perceptions (56,7%) of primary school children in rural areas (53,8%). Primary school children in urban areas have a positive perception about the dangers of smoking to health, No Smoking Area, and the myth of cigarettes. Primary school children in rural areas have a negative perception about No Smoking Area, chewing tobacco, cigarettes danger to the teeth, cigarette advertising, and the myth of cigarettes. Conclusion : There are differences in the perception of primary school children in urban and rural areas about the dangers of smoking with p = 0.000.